Preoperative and Postoperative Photographs and Surgical Outcomes of Patients With Kyphosis. Issue 19 (1st October 2016) - Albayrak, Akif; Balioglu, Mehmet Bulent; Misir, Abdulhamit; Kargin, Deniz; Tacal, Mehmet Temel; Atici, Yunus; Kaygusuz, Mehmet Akif
Abstract : Study Design: A retrospective clinical study was performed. Objective: The aim of the study was to show patients their pre- and postoperative body photographs, and determine the effect on postoperative patient satisfaction for thoracic and thoracolumbar sharp and round angular kyphosis. Summary of Background Data: Previous studies have reported the normative values of pelvic sagittal parameters and the classification of normal patterns of sagittal curvature, but no study has investigated and compared the clinical photographs of sharp and round kyphosis. Methods: In patients who underwent surgery for thoracic and thoracolumbar sharp and round angular kyphosis, whole spine anteroposterior and lateral radiographs, and clinical photographs were obtained preoperatively and at the final follow-up. Pelvic and spinal parameters were measured, and the pre- and postoperative photographs were shown to patients. The Scoliosis Research Society 22r (SRS22r) and Short Form 36 surveys were administered to all patients, and the scores were analyzed. Results: Thirty-eight patients diagnosed with kyphosis (mean age 19.6 yr, mean follow-up duration 26.4 mo) were divided into two groups: sharp (18 patients, mean age 20.1 yr) and round (20 patients, mean age 19.6 yr) kyphosis. There was no difference between values in the sharp and round groups in terms of age, follow-up duration, and Risser score ( P  > 0.05). In both groups, the subscores for pain, self-image, mental health, and satisfaction, except for the function/activity score, and the total score of the SRS22r survey were, however, significantly different between pre- and postoperative photographs. In addition, there was no significant difference between the two groups in any SRS22r domain and Short Form 36 scores. Conclusion: The surgical treatment of kyphosis was uniformly associated with improved quality of life, regardless of the kyphosis type. Thus, showing patients their pre- and postoperative photographs may enhance patient satisfaction, as measured by SRS22r scores. Level of Evidence: 4